The Whoosh of Gadoosh - Skene, Pat 1945-; Keith, Doug, 1952- (Bellevue, WA : Illumination Arts Pub., 2002)
Gadoosh, a purple-haired homeless woman who can magically float aloft on the laughter of children, finds a home in a hospital.
Accelerated Reader AR